The Effect of Risk Profile, Profitability, and Capital on Profit Growth of Indonesian Digital Banks - Yulianingsih, Tanti; Listiana, Erna; Malini, Helma; Wendy; Giriati (Ilomata International Journal of Management, 2024)
Digital Bank is a bank innovation that is very popular today because it provides convenience in transactions. The large number of digital bank enthusiasts makes researchers interested in researching the health of digital banks. This study will investigate how much influence the bank's health level has on the profit growth of digital banks, as measured by the risk profile using NPL and LDR indicators, GCG with institutional ownership, Profitability with ROA indicators, and Capital with CAR indicators. This study utilized panel data regression analysis techniques. The Population in this study are all digital banks registered on IDX, and sampling was performed using purposive sampling techniques, so there are nine banks as a sample from 20 banks. Secondary data research using documentation study methods and literature studies for data collection. This study relies on financial statements obtained from the official web pages of every digital bank and www.idx.co.id as its data source. The research results obtained are ROA was discovered to have a statistically significant positive impact on profit growth, while NPL, LDR, CAR, and GCG had no impact. LDR and ROA were discovered to have a statistically significant positive impact on GCG, whereas NPL and CAR had no impact. According to indirect testing, GCG could not mediate the relationship between NPL, LDR, ROA, and CAR on profit growth.